Congenital adrenal hyperplasia-induced central precocious puberty: Importance of early recognition and treatment - Hossain, Md. Ashraful; Tofail, Tania; Hoque, Ahmad Monirul; Koirala, Satya Prasad; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
One of the commonest causes of peripheral precocious puberty in boys is congenital adrenal hyperplasia (CAH). Hydrocortisone treatment typically prevents peripheral precocity from progressing. However, a small number of patients may develop central precocious puberty while receiving this therapy. In this situation, gonadotropin-releasing hormone analogue (GnRHa) therapy typically arrests subsequent pubertal progression and advancement of bone age. Here, we present a boy with peripheral iso-sexual precocious puberty due to CAH presented at eight years. Since the age of six years, he had a history of the appearance of pubic hair, penile lengthening, offensive behaviour, and gradual darkening of skin. However, his pubertal development and bone age advancement persisted even after conventional treatment with hydrocortisone and fludrocortisone. Conversion to central precocious puberty was subsequently confirmed by clinical and hormonal evaluation. Further, pubertal progression was successfully arrested with a GnRHa in addition to a glucocorticoid and mineralocorticoid regimen. Delayed diagnosis and treatment of CAH may be complicated by true precocious puberty, which can be successfully arrested by treatment with GnRHa along with hydrocortisone and fludrocortisone. [J Assoc Clin Endocrinol Diabetol Bangladesh, July 2026; 5 (2): e87119]